Air purifier using super-absorbent polymer for removing air contaminants. Issue 3 (June 2022) - Yeo, Yong Ho; Gawk, Min A; Lee, Su Yeon; Nam, Young Sik; Park, Won Ho
Abstract: Rapid urbanization and industrialization has caused air pollution primarily in the form of fine dust. Consequently, various respiratory diseases in humans and social damage have increased. Interest in air purifiers for removing particulate matter (PM) is increasing rapidly. However, multiple filters must be employed in a dry air purifier because the PM is extremely fine. The pores in filters are filled with PM after a certain duration; as such, commercial filters need to be replaced because their filtration efficiency decreases when used for a long period of time. This causes an increase in cost and secondary environmental pollution. A wet air purifier should be developed to compensate for the disadvantages of dry air purifier. A wet air purifier uses water-based filters, which can effectively remove air contaminants. In addition, water can dissolve and remove ammonia gas, which is a representative odorous substance. In this study, a wet air purifying system is designed using super-absorbent polymer (SAP) beads containing high amounts of water. The removal efficiencies of fine dust (PM1.0, PM2.5, and PM10 ) and odorous substances (NH3 ) are investigated using SAP beads of different sizes, and the reusability of the SAP beads is examined. Graphical Abstract: ga1 Highlights: Interest in air purifiers for removing particulate matter (PM) is increasing rapidly. Novel wet-type air purifier was proposed to compensate for the disadvantages of air purifier. Wet air purifier is designed using super-absorbent polymer (SAP) beads containing high water. The removal ability and reusability of SAP beads against PM and ammonia gas was excellent.